Health Plan Design: A Way to Risk Assessment or Risk Avoidance? A Comparison towards Private Health Insurance Products and Services of Selected Firms in the US and the UK - Wu, Si (2007)
Many observations suggest that the health insurance market rewards those health plans that manage to sell the largest percentage of their product to people who need it the least, and avoid those likely to use it the most. That means health insurers develop health insurance plans in such a way that plans are attractive to the low risk individuals but at the expense of coverage to the high risk type. The strategies that they use are in setting the rates to risk selection and classification, underwriting and utilization management. They also concern with the supply side of service the providers, and monitor the way that they behave to control services utilization and cost. However, the conduct of such strategies are varied in the US and UK due to the different market and regulation environments.